Encyclopedia of criminology - Wright, Richard A. (Richard Alan) 1953-; Miller, J. Mitchell (Routledge, 2005)
This three-volume work offers a comprehensive review of the pivotal concepts, measures, theories, and practices that comprise criminology and criminal justice.